PENGARUH PENGGUNAAN WEBSITE TERHADAP CITRA PROVIDER TELKOMSEL BATAM - Narti Eka Putria (Computer Based Information System Journal, 2013)
This study aimed to examine the effect of the use of the image of the website provider Telkomsel Telkomsel. Telkomsel provider imagery can be interpreted as a result of the company or individual in carrying out its work effectively, efficiently and legally controlled undertaken in order to achieve the mission and vision of the company At the beginning of the PT. Telkomsel is a joint venture between PT. Telkom and PT. Indosat engaged in telecommunications. By name in November 1993 Telkomsel PT. Telkom implement the Pilot Project on the island of Batam and Bintan islands by using the system of the European digital technology, known as GSM. Treading December 1993 PT. Telkom officially registered as a member of the GSM MOU and the beginning of the first telecommunications between phones on the island of Batam and Bintan islands. The project succeeded in building a mobile telecommunications network from scratch in a relatively short period of time is just over two months. Telkomsel is the leading mobile telecommunications operator in Indonesia that provides a variety of technology-based services with GSM network Dual Band (900 & 1800), GPRS, Wi - Fi, EDGE, 3G, HSDPA and HSPA in Indonesia. For international network, Telkomsel collaborate with 362 roaming partners in 196 countries. State-owned company between PT. Telkom and PT. Indosat finally formed in November 1994. The project evolved into other provinces in Indonesia which eventually led to the establishment of PT. Telkomsel on May 26, 1995 as one of three national license holders GSM operators in Indonesia. After a tender process open and transparent for approximately one year, entry of new shareholders, namely PT. Telecom Netherlands and PT. SETCO Megacell Asia. Until now the final composition of PT. Telkomsel held by two companies, namely PT. Telkom and PT by 65%. SingTel (Singapore Telecom) by 35%. With the shareholding structure of the PT. Telkomsel will be very easy to access and continuity of political, global communications, total quality control and GSM access between countries, as well as promotion and others.